Clinical application and verification of the TG13 diagnostic and severity grading criteria for acute cholangitis: an international multicenter observational study. (29th May 2017) - Kiriyama, Seiki; Takada, Tadahiro; Hwang, Tsann‐Long; Akazawa, Kohei; Miura, Fumihiko; Gomi, Harumi; Mori, Rintaro; Endo, Itaru; Itoi, Takao; Yokoe, Masamichi; Chen, Miin‐Fu; Jan, Yi‐Yin; et al.
Abstract: Background: The Tokyo Guidelines 2007 (TG07) first presented the diagnostic and severity grading criteria for acute cholangitis. Subsequently updated in 2013, the Tokyo Guidelines (TG13) have been widely adopted throughout the world as global standard guidelines. We set out to verify the efficacy of these TG13 criteria in an international multicenter study. Methods: We reviewed 6, 063 patients who were clinically diagnosed with acute cholangitis in Japan and Taiwan over a 2‐year period. The TG13 diagnostic and severity grading criteria were retrospectively applied, and 30‐day mortality was investigated. Results: A diagnosis of acute cholangitis was made in 5, 454 (90.0%) patients on the basis of the TG13 criteria, and in 4, 815 (79.4%) patients on the basis of the TG07 criteria. The 30‐day mortality rates of patients with Grade III, Grade II, and Grade I were 5.1%, 2.6%, and 1.2%, respectively, and increased significantly along with disease severity. The mortality rate in the 1, 272 Grade II cases where urgent or early biliary drainage was performed was 2.0% ( n = 25), which was significantly lower than that of 3.7% ( n = 28) in the other 748 cases. Conclusion: By using the TG13 diagnostic and severity grading criteria, more patients with possible acute cholangitis can be diagnosed, and patients whose prognosis can potentially be improved by early biliary drainage can be identified. The TG13 criteria are appropriate and useful for clinical practice. Abstract : Highlight Kiriyama and colleagues set out to verify the efficacy of the TG13 diagnostic and severity grading criteria in an international multicenter study. The TG13 criteria enable more patients with possible acute cholangitis to be diagnosed and patients whose prognosis can potentially be improved by early biliary drainage to be identified.